2019
DOI: 10.1186/s12859-018-2373-1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse dynamics features of novel protein kinase C (PKC) isozymes determine the selectivity of a fluorinated balanol analogue for PKCε

Abstract: Background: (−)-Balanol is an ATP-mimicking inhibitor that non-selectively targets protein kinase C (PKC) isozymes and cAMP-dependent protein kinase (PKA). While PKA constantly shows tumor promoting activities, PKC isozymes can ambiguously be tumor promoters or suppressors. In particular, PKCε is frequently implicated in tumorigenesis and a potential target for anticancer drugs. We recently reported that the C5(S)-fluorinated balanol analogue (balanoid 1c) had improved binding affinity and selectivity for PKCε… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Compound 6 was confirmed in previous studies as a competitive inhibitor of PKA and PKC, lacking selectivity. Most researches on compound 6 have focused on improving its selectivity for PKC and PKA, with few studies of its binding to other kinases [38–40] . By molecular docking, MD simulation and CETSA, we confirmed that compound 6 can bind stably to PAK1.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Compound 6 was confirmed in previous studies as a competitive inhibitor of PKA and PKC, lacking selectivity. Most researches on compound 6 have focused on improving its selectivity for PKC and PKA, with few studies of its binding to other kinases [38–40] . By molecular docking, MD simulation and CETSA, we confirmed that compound 6 can bind stably to PAK1.…”
Section: Discussionmentioning
confidence: 55%
“…Most researches on compound 6 have focused on improving its selectivity for PKC and PKA, with few studies of its binding to other kinases. [38][39][40] By molecular docking, MD simulation and CETSA, we confirmed that compound 6 can bind stably to PAK1. More than that, we found that compound 6 can inhibit ERK and AKT, two key signaling pathways downstream of PAK1, in SW480 cells.…”
Section: Discussionmentioning
confidence: 82%
“…1). Unlike molecular docking, MD simulations allow ligands and M pro to move and interplay, adjusting their intermolecular interactions [23,25]. According to molecular docking results, N3 and leupeptin display two unfavorable interactions with M pro (Table 2, Fig.…”
Section: Non-bonded Interactions Between M Pro and Ligandsmentioning
confidence: 99%
“…Hence, another method, such as molecular dynamics (MD) simulation, should be implemented after the molecular docking step to obtain a more accurate prediction of energy and conformation. MD simulations have been employed in many studies of protein-ligand interactions [23][24][25].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bioinformatics provides solutions to predicting the 3D structures of proteins that so not have experimental structures. Hardianto et al [23] have used homology models of novel protein kinase C (PKC) isozymes to characterize their interaction with a candidate inhibitory drug molecule. On the other hand, Borah and Jha [24] have predicted an ab initio structural model for a pathogenic protein, HopS2, that affects tomato plants, to understand its pathogenic function, as a Type III secretion system.…”
Section: Structural Bioinformaticsmentioning
confidence: 99%